Improving Communication in Outpatient Consultations in People With Cirrhosis: The Development of a Question Prompt List (QPL). Issue 10 (November 2020) - Low, Joseph T.S.; Davis, Sarah; Greenslade, Lynda; Carroll, Cathy; Craig, Rachel; Wilson, Jo; Clancy, Jennifer-Louise; Marshall, Aileen; Thorburn, Douglas; Stone, Patrick
Abstract : Background and Aims: Liver health professionals have difficulty discussing liver cirrhosis and its prognosis with patients and families. Question Prompt Lists (QPLs), which are evidence-based lists of "recommended questions, " may improve communication but need to be designed specifically for the target population. This study aimed to develop and pilot a QPL for patients with cirrhosis. Methods: A mixed-methods design in 3 phases. In phase 1 (item generation), potential questions for inclusion in the QPL were identified from 3 sources—a scoping literature review; an online survey; and interviews with patients, family members, and health professionals. In phase 2 (QPL construction), a multidisciplinary expert panel finalized the selection of questions and the format of the QPL. In phase 3 (pilot study), the QPL was assessed for acceptability and feasibility in a hepatology outpatient clinic population. Results: From 258 topics initially identified, 30 questions were included in the first draft of the QPL. After review by a multidisciplinary expert panel including patients, the QPL was reduced to 22 questions. In the pilot study, 133/215 eligible patients consented to participate, although only 67/133 used the QPL in their clinic appointment. Among those who used the QPL, all questions were asked at least once. The most commonly asked question related to life expectancy. Most participants expressed support for the content of the QPL. Conclusions: A QPL, suitable for use in patients with liver cirrhosis attending hepatology outpatient clinics, has been developed and piloted. The QPL seems to be feasible to use and acceptable to patients and clinicians. Further work is needed to evaluate its effectiveness and to determine optimum delivery in clinical practice. Abstract : Supplemental Digital Content is available in the text.